Mantap boi service / Azammudin A. Bakar ... [et al.] - A. Bakar, Azammudin; Annuar, Akmal Zulhilmi; Abdul Aziz, Omar; Abdul Rahim, Liyana Batrisya; Julia, Joharis (2021)
Mantap Boi Service is a company which focuses on the servicing all home appliances. The home appliances is television, washing machine and freezer. This service will be cover at the near with Petaling Jaya and we will provide service pick- up from home to my shop. We will provide service repairing at customer house. We can fix the customer problem at the house because customer can look what we fix there thing and give the satisfaction to the customer. This company service is different with another company because this company provide the female technician to give the comfortable to the female customer. This company brave to make the different thing because some customer not comfortable with male technician. The different thing make the company sales is increase because many customer contact to ask about the female technician. The feedback from customer is good.